Mice mucosal leishmaniasis model shown high parasite load, increased cytotoxicity and impaired IL-10+ T cell response - Da-Rocha, Alisson Amaral; Dos-Santos, Júlio Souza; Bittencourt, Igor Santos; De-Almeida, Douglas B.; Manhães, Naiara Carla dos Santos; Praxedes, Hozany; Romano, João Victor Paiva; da Silva-Junior, Elias Barbosa; da Silva-Gonçalves, Antônio José; Oliveira, Marcia Pereira; Covre, Luciana Polaco; Gomes, Daniel Claudio de Oliveira; et al. (Frontiers in Immunology, 2025)
Mucosal Leishmaniasis is one of the most aggressive clinical manifestations of Leishmania infection disease, characterized by the destruction of nasal and oral tissues. The mechanisms by which this disease occurs are still not well understood due to the lack of effective experimental models. Mucosal leishmaniasis is associated with inflammatory response, especially Th17 response. Based on that, in this work, the immunopathological aspects of the experimental infection of BALB/c mice by Leishmania amazonensis in the mucosa site were evaluated as this mice presents high susceptibility with increased Th17 mediated pathology. Three infection modes were performed and compared according to the injection site. Six weeks post infection, mice presented edema in the nasal and premaxillary region, with progressive growth until twelve weeks. The micro-Computerized Tomography and the histology images demonstrated that the parasite inoculation led to destruction of squamous and transitional tissues in NC and NB groups, with several cells harboring amastigotes. Mice infected in the mucosa tissues had higher parasite load and IgG, IgM antibody levels and increased production of cytotoxic mediators such as CD107, granzyme b and perforin, inflammatory cytokines as IFN-γ; and IL-17, but lower frequencies of CD4+ IL-10+ cells compared to ear dermis. Taken together, our data shows that L. amazonensis parasites are more proliferative in nasal mucosa and the infection leads to an increased inflammatory response compared to ear dermis, suggesting an imbalance between the inflammatory and regulatory response in the mucosa as occurs in human MCL which point this model as an interesting approach to understand some features of the disease immunopathology. Further studies are being performed to understand the Th1-mediated tissue destruction. This study was conducted in accordance with the local legislation and institutional requirements being approved by the Ethics Committee on the Animal Use in Experimentation - under the protocol CEUA No. 133/23 of the Health Sciences Center (CCS) from the University of Rio de Janeiro.